Prospective evaluation of acute toxicity and patient reported outcomes in anal cancer and plan optimization. Issue 2 (August 2018) - Kronborg, Camilla; Serup-Hansen, Eva; Lefevre, Anna; Wilken, Eva E.; Petersen, Jørgen B.; Hansen, Jolanta; Schouboe, Annette; Nyvang, Lars; Spindler, Karen-Lise G.
Abstract: Background and purpose: Chemoradiotherapy (CRT) is the standard therapy for localized anal cancer (AC), but this treatment is associated with substantial toxicity. However, there is a lack of prospectively collected toxicity and patient reported outcome (PRO) data from larger cohorts. The purpose was to prospectively collect and determine agreement between physician assessed toxicity (CTCAE) and PRO during and after CRT and to compare IMRT, VMAT and proton-based planning in a subgroup of patients. Material and methods: Patients, treated with CRT for AC, were included between 2015 and 2017. NCI-CTCAE v.4.0, EORTC QLQ-C30 and CR29 data were collected baseline, mid-therapy, end-of therapy and 2–4 weeks posttherapy. Treatment planning with 5- or 6-fixed field IMRT, 2 and 3 arc VMAT, and 3- and 4-field proton plans were compared. Results: One-hundred patients were included. Both CTCAE and PROs related to acute toxicity reached a maximum at end of therapy. Incidences of PROs were markedly higher with only slight to fair agreement to CTCAE, (κ 13–37). Comparative planning revealed dosimetric equality of IMRT and VMAT plans, but superiority of proton plans. Conclusions: The high incidence of PRO scores and weak agreement to CTCAE suggest that PROs are important tools complementary to CTCAE in evaluating patient symptoms during and after CRT. Proton therapy has the potential to lower radiation doses to most organs at risk.